ANALISIS PERTUMBUHAN EKONOMI INDONESIA TAHUN 2014-2021 DENGAN INDEKS PEMBANGUNAN MANUSIA DAN INFLASI - Alfira Nabila; Didit Welly Udjianto (International Journal of Multidisciplinary Research and Literature, 2023)
High economic growth can indicate an improvement in the populace's well-being due to the increased production that increases public consumption. Several factors, including the Human Development Index (HDI) and inflation, can affect economic growth. This study aims to analyze the effect of the human development index and inflation on Indonesia's economic growth from 2014 to 2021. The development index and inflation both served as independent variables for this investigation. The rate of economic growth serves as the dependent variable. The data analysis method is descriptive quantitative, and there were 96 observations in the sample. According to the findings of this research, the Human Development Index has a favorable and significant effect, whereas inflation has an unfavorable and negligible effect